1974
DOI: 10.1172/jci107871
|View full text |Cite
|
Sign up to set email alerts
|

Normal Contractile State of Hypertrophied Myocardium after Pulmonary Artery Constriction in the Cat

Abstract: A B S T R A C T The contractile function of right ventricular papillary muscles from normal cats and cats in which the pulmonary artery had been constricted for 6 or 24 wk was examined. Acute pulmonary artery constriction reduced cross-sectional area by an average of 70%, resulting in a 30% mortality from congestive heart failure, all such deaths occurring within the first 3 wk after banding. The increase in right ventricular mass in animals surviving for 6 or 24 wk was similar, averaging 70%. No banded animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0

Year Published

1975
1975
1989
1989

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(25 citation statements)
references
References 21 publications
4
21
0
Order By: Relevance
“…Comparison of ventricular weights, papillary muscle cross-sectional area, and hemodynamics among groups is presented in Table I. Nonbanded control animals studied after 24 wk of observation had right ventricular-to-body weight ratios and left ventricular-to-body weight ratios significantly smaller than animals observed for 6 wk, as reported previously (20). These differences appear to be due to an increase in body fat during prolonged inactivity rather than any dimunition in mass of the heart since the liver-to-body weight ratios in the 24-wk control animals were also significantly less than those of the 6-wk controls.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Comparison of ventricular weights, papillary muscle cross-sectional area, and hemodynamics among groups is presented in Table I. Nonbanded control animals studied after 24 wk of observation had right ventricular-to-body weight ratios and left ventricular-to-body weight ratios significantly smaller than animals observed for 6 wk, as reported previously (20). These differences appear to be due to an increase in body fat during prolonged inactivity rather than any dimunition in mass of the heart since the liver-to-body weight ratios in the 24-wk control animals were also significantly less than those of the 6-wk controls.…”
Section: Resultssupporting
confidence: 76%
“…We previously reported that sudden sustained pulmonary artery banding in the cat resulted in depression of contractile state 6 wk after banding with subsequent recovery of normal contractile function by 24 wk after constriction (20). In the present study values for peak force and maximal dF/dt in the 6 wk banded treated group were comparable to those of untreated nonbanded animals indicating that digitoxin significantly enhanced the rate of recovery of myocardial function after banding.…”
Section: Discussionsupporting
confidence: 71%
“…At 2 wk dense fibrosis was found around the band and we suspect that an inflammatory reaction reduced pulmonary artery diameter more quickly than anticipated. Nevertheless, both the load and hypertrophy occurred more slowly in this model than in a banded adult cat model used previously in our laboratory (17). We examined seven additional kittens 1 wk after banding in a similar manner and found the RV systolic pressure averaged 40±4.0 mm Hg and the RV/LV ratio 0.38±0.03, whereas in six adult cats 1 wk after banding in the more standard manner (17) RV systolic pressure and RV/LV averaged 48±4 mm Hg and 0.49±0.02, respectively, both values being significantly greater (P < 0.05) than their respective values in kittens banded for 1 wk.…”
Section: Discussionmentioning
confidence: 54%
“…This preparation does not permit sampling of the venous effluent from the hypertrophied right ventricle, thus direct measurements of right ventricular oxygen consumption are not possible. However, heart rate, ventricular wall tension, contractility, and afterload (19,20) or no change (1,(21)(22)(23) in contractile activity of the hypertrophied heart. Because the observed increases in blood flow are specific to the right ventricle,' it is likely that a major determinant of this increased blood flow is the increased external work that must be performed by the right ventricle to maintain function in the face of the pressure overload.…”
Section: Methodsmentioning
confidence: 99%